A Novel Long-circulating DOX Liposome: Formulation and Pharmacokinetics Studies - Xiao, Peihong; Zhao, Juan; Huang, Yi; Jin, Rongrong; Tang, Zhonglan; Wang, Ping; Song, Xu; Zhu, Hongfei; Yang, Zibin; Yu, Nie (Pharmaceutical Nanotechnology, 2020)
Background: Doxorubicin (DOX) is a leading chemotherapeutic in cancer treatment because of its high potency and broad spectrum. Liposomal doxorubicin (Doxil®) is the first FDA-approved PEG-liposomes of DOX for the treatment of over 600,000 cancer patients, and it can overcome doxorubicin-induced cardiomyopathy and other side effects and prolong life span. The addition of MPEG2000-DSPE could elevate the total cost of cancer treatment. Objective: We intended to prepare a novel DOX liposome that was prepared with inexpensive materials egg yolk lecithin and Kolliphor HS15, thus allowing it to be much cheaper for clinical application. Methods: DOX liposomes were prepared using the combination of thin-film dispersion ultrasonic method and ammonium sulfate gradient method and the factors that influenced formulation quality were optimized. After formulation, particle size, entrapment efficiency, drug loading, stability, and pharmacokinetics were determined. Results: DOX liposomes were near-spherical morphology with the average size of 90 nm and polydispersity index (PDI) of less than 0.30. The drug loading was up to 7.5%, and the entrapment efficiency was over 80%. The pharmacokinetic studies showed that free DOX could be easily removed and the blood concentration of free DOX group was significantly lower than that of DOX liposomes, which indicated that the novel DOX liposome had a certain sustainedrelease effect. Conclusion: In summary, DOX liposome is economical and easy-prepared with prolonged circulation time. Lay Summary: Doxorubicin (DOX) is a leading chemotherapeutic in cancer treatment because of its high potency and broad spectrum. Liposomal doxorubicin (Doxil®) is the first FDAapproved PEG-liposomes of DOX to treat over 600.000 cancer patients, overcoming doxorubicin- induced cardiomyopathy and other side effects and prolonging life span. The addition of MPEG2000-DSPE could elevate the total cost of cancer treatment. We intend to prepare a novel DOX liposome prepared with inexpensive materials egg yolk lecithin and Kolliphor HS15, thus allowing it to be much cheaper for clinical use. The novel DOX liposome is economical and easy-prepared with prolonged circulation time.
Keywords: entrapment efficiency